Characteristics and outcomes of older patients with secondary acute myeloid leukemia according to treatment approach. Issue 16 (7th April 2017) - Boddu, Prajwal Chaitanya; Kantarjian, Hagop M.; Ravandi, Farhad; Garcia‐Manero, Guillermo; Verstovsek, Srdan; Jabbour, Elias J.; Takahashi, Koichi; Bhalla, Kapil; Konopleva, Marina; DiNardo, Courtney D.; Ohanian, Maro; Pemmaraju, Naveen; et al.
Abstract : BACKGROUND: The development of newer strategies to improve outcomes for older patients with secondary acute myeloid leukemia (s‐AML) is a critical unmet need. Establishing baseline metrics for evaluating newer approaches is important. METHODS: s‐AML was defined as 1 or more of the following: a history of an antecedent hematologic disorder (AHD), a diagnosis of therapy‐related acute myeloid leukemia (AML), and AML with karyotype abnormalities characteristic of myelodysplastic syndrome. Newly diagnosed s‐AML patients aged 60 to 75 years were grouped into 5 treatment cohorts: 1) patients receiving high‐ or intermediate‐dose cytarabine–based intensive chemotherapy (IC), 2) patients receiving a hypomethylating agent (HMA) or HMA combinations, 3) patients receiving low‐dose cytarabine (LDAC) combinations, 4) patients receiving CPX‐351, and 5) patients receiving investigational (INV) agents. Nine hundred thirty‐one patients met the age and s‐AML criteria. RESULTS: Complete remission rates were statistically lower in the HMA group (36%) versus the IC (46%), CPX‐351 (45%), and LDAC groups (43%). Patients receiving less intensive regimens (the HMA and LDAC groups combined) had superior overall survival (OS) in comparison with patients receiving IC‐based regimens (median 6.9 vs 5.4 months; P = .048). Only 4.3% of the IC patients proceeded to transplantation, whereas 10.3% of the patients on lower intensity regimens did ( P = .001). There was no difference in median survival between patients treated with CPX‐351 and patients treated with conventional lower intensity approaches ( P = .75). Age > 70 years, an adverse karyotype, and a prior AHD were associated with decreased OS in a multivariate analysis. CONCLUSIONS: Lower intensity approaches are associated with lower early mortality rates and improved OS in comparison with intensive regimens. OS is poor with currently available therapies with a median OS of 6 months (5.4‐7.6 months across regimens). Unsatisfactory outcomes with other INV agents underscore the need for more effective therapies. Cancer 2017;123:3050–60. © 2017 American Cancer Society . Abstract : Lower intensity (ie, low‐dose cytarabine–based and hypomethylating agent–based) approaches are associated with lower early mortality and improved overall survival in comparison with intensive regimens in older patients with secondary acute myeloid leukemia. CPX‐351 is not statistically associated with superior median survival in comparison with lower intensity therapy approaches to secondary acute myeloid leukemia.